HRCT Chest in Patient of COVID-19 Pneumonia at a Tertiary Care Hospital of Central Nepal - Acharya, Rajesh; Chhetri, Pramod Kumar; Prasad, V. Natraj; Akhtar, Kalim; Thapa, Kripesh; Mishra, Manish; Ghimire, Arati (Journal of College of Medical Sciences-Nepal, 2022)
Background: COVID19 pneumonia is caused by novel corona virus. The HRCT chest is helpful in identification of COVID-19 Pneumonia. CT chest play a crucial role in assessing the pattern of manifestation and severity of lung involvement in COVID-19. The objective of this study is to described high resolution computed tomography (HRCT) chest findings in COVID-19 Pneumonia patients in college of medical sciences Bharatpur Nepal. Method: A prospective, HRCT Chest findings were analaysed in 375 patients. Patients with high CORADS score and suspicious for COVID-19 pneumonia were further tested positive in PCR examination. The study was done for a year period of time Result: A total 375 patients suspected for COVID-19 pneumonia in HRCT, 341 were PCR positive. The mean age affected by viral pneumonia was 51.9 (51-60 year group). The male were 240 and female were 135. Ground glass opacities is noted in 188 patients, followed by GGO and consolidation in 177, consolidations only in 7 and others findings chest findings in 3 patients. Conclusion: HRCT chest can help in early detection of COVID-pneumonia. It can also asses the percentages of lung involvement and severity of disease that can guide physician.